2019
DOI: 10.3390/rs11091094
|View full text |Cite
|
Sign up to set email alerts
|

Crop Sensor-Based In-Season Nitrogen Management of Wheat with Manure Application

Abstract: It is difficult to predict the crop-available nitrogen (N) from farmyard manures applied to soil. The aim of this study was to assess the usefulness of the proximal sensors, Yara N-TesterTM and RapidScan CS-45, for diagnosing the N nutritional status of wheat after the application of manures at sowing. Three annual field trials were established (2014–2015, 2015–2016 and 2016–2017) with three types of fertilizer treatments: dairy slurry (40 t ha−1 before sowing), sheep manure (40 t ha−1 before sowing) and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…A previous study showed a good relationship between leaf N concentration and measurements taken with chlorophyll meters [7][8][9]. Chlorophyll meters and wheat grain yield were related in different studies and used to identify responses to additional fertilizers [9,10] and for recommendations on fertilizer management [11][12][13]. Moreover, the possibility of using chlorophyll meters to decide if an extra fertilizer dose is required to increase GPC has been studied [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed a good relationship between leaf N concentration and measurements taken with chlorophyll meters [7][8][9]. Chlorophyll meters and wheat grain yield were related in different studies and used to identify responses to additional fertilizers [9,10] and for recommendations on fertilizer management [11][12][13]. Moreover, the possibility of using chlorophyll meters to decide if an extra fertilizer dose is required to increase GPC has been studied [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, multiple studies have used POSs to monitor N content, as well as to predict seed yields of winter wheat, observing a correlation between NDVI and N uptake with seed yield at harvest [22][23][24][25][26][27][28][29][30]. For instance, Inman et al [24] found that NDVI was useful for estimating grain yields of irrigated maize, while canopy cover readings, at the late-filling stage, were useful for predicting winter wheat yields.…”
Section: Introductionmentioning
confidence: 99%
“…Three field trials were established in Arkaute (Araba, Basque Country, Spain) at NEIKER facilities in three consecutive wheat growing seasons defined as 2015, 2016, and 2017 in different fields under rainfed conditions. The three field trials were flat, presented similar characteristics, and the distance among them was 130 m. Other soil properties were described previously [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the treatments, two controls were established ( Table 3 ): A control without N fertilisation (0 N), and an overfertilised control plot (280 N). Information regarding the organic manure characteristics and application was previously described [ 33 ]. Soft wheat ( Triticum aestivum var.…”
Section: Methodsmentioning
confidence: 99%